Natural activators of adenosine 5′-monophosphate (AMP)-activated protein kinase (AMPK) and their pharmacological activities. (December 2018) - Vazirian, Mahdi; Nabavi, Seyed Mohammad; Jafari, Samineh; Manayi, Azadeh
Abstract: Adenosine 5′-monophosphate (AMP)-activated protein kinase (AMPK) is a heterotrimeric enzyme which monitors cellular energy status and regulates metabolism with energy balance. AMPK activation, as a master regulator of metabolism, plays role in key tissues like liver, skeletal muscles, and heart as well as central nervous system (CNS). Activation of the enzyme by indirect activators attracts scientific attentions to treat diabetes, obesity, cancer, and other related metabolic disorders like physiological and pathophysiological states in CNS. A number of hormones and pharmacological agents have been reported to activate AMPK including paroxetine, metformin, thiazolidinediones, adiponectin, leptin, interleukin-6, and etc. AMPK activity is prominent in regulation of glucose, lipid, and proteins metabolism as well as mitochondrial biogenesis and autophagy. Activation of AMPK in the liver decrease blood glucose and in skeletal muscles stimulates glucose uptake independently of insulin through modulation of activity of several downstream substrates. Activation of AMPK inhibits synthesis and induces oxidation of fatty acids, which may reduce ectopic lipid accumulation and improve insulin action. The enzyme activation promotes cardiovascular homeostasis by ensuring optimum redox balance of heart and vascular tissue. In addition, AMPK signaling may link to cancer development via regulation of checkpoints of cell cycle. Numerous of conventional drugs have been derived from natural resources, while the application of this fruitful source of chemical structures have not been explored in depth. A number of these compounds are discussed in this review that exhibit beneficial effects in metabolic disorders through AMPK activation.